2023
DOI: 10.1364/josab.483574
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of electron vortices in photoionization of molecules and atoms by counter-rotating circularly polarized laser pulses

Abstract: We comparatively study the effect of orbital symmetry on vortex patterns in photoelectron momentum distributions (PMDs) of perfectly aligned H2 and N2 molecules and their companion atom Ar exposed to a pair of delayed counter-rotating circularly polarized lasers by numerically solving the two-dimensional time-dependent Schrödinger equation. We show that vortex patterns in PMDs strongly depend on the orbital symmetry of atoms and molecules, and numbers of spiral arms in PMDs of N2, H2, and Ar are quite differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The generation of vortex-shaped photoelectron wave packets in the photoionization of helium atoms [13,28] and hydrogen molecular ions [29] has been proposed by employing timedelayed counter-rotating circularly polarized attosecond pulses. In addition to the time delay, researchers have also explored the control of other laser parameters, such as the carrier-envelope phase (CEP) [17,27], relative optical phase [25,30], polarization state [13,23,28,31,32], orbital symmetry [33,34], and chirp [35]. Moreover, vortices have not only been observed in photoionization but also in photodissociation [29] and photodetachment [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The generation of vortex-shaped photoelectron wave packets in the photoionization of helium atoms [13,28] and hydrogen molecular ions [29] has been proposed by employing timedelayed counter-rotating circularly polarized attosecond pulses. In addition to the time delay, researchers have also explored the control of other laser parameters, such as the carrier-envelope phase (CEP) [17,27], relative optical phase [25,30], polarization state [13,23,28,31,32], orbital symmetry [33,34], and chirp [35]. Moreover, vortices have not only been observed in photoionization but also in photodissociation [29] and photodetachment [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the CRTC fields and corotating twocolor (CoRTC) fields have been used to control nonsequential double ionization (NSDI) [27,28], investigate nonadiabatic offsets of the initial electron momentum distribution in strongfield tunnel ionization [29], and observe experimentally subcycle interference structures in the photoelectron momentum distributions (PEMDs) [30,31], etc. Additionally, it has been shown that PEMDs generated by bicircular laser fields carry the information about the molecular orientation and structure [32][33][34].…”
Section: Introductionmentioning
confidence: 99%